THE DEATH PENALTY AND ETHICS - Sharma, Minakshi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The execution of a person who has been found guilty of a crime by the state is known as the capital penalty. The usefulness of this punishment is hotly contested in today’s culture. The moral perspective of abolitionists holds that the death sentence is unethical because it violates human rights and can lead to biased sentencing. The "eye-to-eye approach" and the "deterrent theory" are the main arguments used by proponents of the death penalty to support their position. However, some Indian court rulings have emphasized the "rarest of the rare" situations for which this type of punishment ought to be applied.